Description of three new species of Isoctenus Bertkau, 1880 and new records for I. areia Polotow & Brescovit (Araneae, Ctenidae) from northeastern Brazil - Moraes, Isadora M. Pontes; Polotow, Daniele; Labarque, Facundo M.; Silva, Marcio B. Da (Zootaxa, 2023)
Three new species of the genus Isoctenus Bertkau, 1880 are described from the state of Bahia, in the northeast of Brazil: Isoctenus jussara new species, Isoctenus cabula new species, and Isoctenus botocudos new species. In addition, new records of Isoctenus areia Polotow and Brescovit, 2009 are presented. Previously known only from the city of Areia, state of Paraíba, its distribution now expands to the cities of Mamanguape, state of Paraíba, and Igarassu, state of Pernambuco.